2011
DOI: 10.2460/ajvr.72.9.1204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hematocrit on accuracy of two point-of-care glucometers for use in dogs

Abstract: Hct had a relevant impact on the correlation between whole blood and plasma glucose concentrations in dogs. Significant variations between results obtained with the 2 glucometers could be critical when interpreting blood glucose measurements or selecting a POC glucometer for an intensive care setting and precise glycemic control in critically ill dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 17 publications
8
42
0
Order By: Relevance
“…Results of other studies [11][12][13][14] suggest that Hct significantly affects the measurement of whole blood glucose concentration by a POCG in dogs, cats, and humans. Results indicated that the correlation between the whole blood glucose concentration measured by the POCG and the serum glucose concentration measured by the biochemical analyzer was significantly better for canine samples with a PCV < 40%, compared with that for canine samples with a PCV within the reference range.…”
Section: Discussionmentioning
confidence: 95%
“…Results of other studies [11][12][13][14] suggest that Hct significantly affects the measurement of whole blood glucose concentration by a POCG in dogs, cats, and humans. Results indicated that the correlation between the whole blood glucose concentration measured by the POCG and the serum glucose concentration measured by the biochemical analyzer was significantly better for canine samples with a PCV < 40%, compared with that for canine samples with a PCV within the reference range.…”
Section: Discussionmentioning
confidence: 95%
“…Blood glucose values determined by most PBGM devices designed for use in human diabetics are typically lower than actual glucose values determined by reference methods, and the difference between the actual glucose value and value obtained from the PBGM increases as hyperglycemia worsens ( Fig. In one study, results of the AlphaTRAK were less accurate compared with a laboratory reference method in blood samples with a lower hematocrit (< 30%) but not an increased hematocrit (> 50%), whereas results from a PBGM for use in humans was less accurate with increased hematocrit but not a decreased hematocrit (Paul et al, 2011). This bias may result in an incorrect diagnosis of hypoglycemia or the misperception that glycemic control is better than it actually is.…”
Section: Protocol For Generating the Serial Blood Glucose Curve In Thmentioning
confidence: 98%
“…7,8,45 Massive leukocytosis can have the same effect. 7,8,45 Massive leukocytosis can have the same effect.…”
Section: Polycythemia and Leukocytosismentioning
confidence: 99%